Antibacterial activity of lactic acid bacteria from various freshwater fish species against pathogenic bacteria in caged red tilapia (Oreochromis sp.) - QUACH VAN CAO THI; TRAN QUOC DUNG; HA NGỌC HIEN; NGUYEN BAO TRUNG; TU THANH DUNG; NGUYEN PHUONG THUY (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Quach VCT, Tran QD, Ha NH, Nguyen BT, Tu TD, Nguyen PT. 2023. Antibacterial activity of lactic acid bacteria from various freshwater fish species against pathogenic bacteria in caged red tilapia (Oreochromis sp.). Biodiversitas 24: 3373-3383. Antibiotic-resistant bacteria are a big challenge for many aquaculture countries around the world. The search for new solutions, such as probiotics to replace antibiotics in aquaculture, attracts the interest of many scientists. The investigation was accomplished by isolating Lactic Acid Bacteria (LAB) inhibiting Streptococcus agalactiae and Aeromonas hydrophila, which cause swollen eyes and hemorrhagic skin disease in caged red tilapia (Oreochromis sp.) in Vinh Long province. The findings isolated 37 isolates of LAB from the intestines of catfish, red tilapia, and tilapia. Using the diffusion well method, the results showed that 13/37 (35.14%) and 18/37 (48.65%) isolates were inhibitory against S. agalactiae and A. hydrophila, respectively. The research found that eight isolates were inhibitory to two species of S. agalactiae and A. hydrophila, especially isolate CT6.2, which has the strongest inhibition (10.5 mm inhibition zone diameter). Our finding revealed that the isolates CT6.2 and RP6 demonstrate the highest antagonistic activity against S. agalactiae and A. hydrophila at a density of 108 CFU/mL after incubation at 35°C, pH = 5-6 for 48-60 h. Using PCR techniques and 16S rRNA gene sequencing combined with morphological and biochemical characteristics, the LAB isolates in the findings belong to the genera Lactobacillus and Pediococcus, being 99.35% and 99.02% similar to Lactobacillus plantarum and Pediococcus pentosaceus, respectively. This is the first report on the antimicrobial activity of LAB against S. agalactiae and A. hydrophila in caged red tilapia in the Mekong Delta.